Influence of Autophagy Induction after Hormone Treatment on Oocytes Maturation of Porcine - Sang Hwan Kim; Jong Taek Yoon (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Here, we evaluated the mode of programmed cell death during porcine oocyte maturation by comparing the two major pathways associated with programmed cell death, apoptosis (type I), and autophagy (type II). We investigated the expression and localization of major genes involved in autophagy and apoptosis at mRNA and protein levels. Furthermore, the effect of hormonal stimulation on autophagy and apoptosis was analyzed. We found that the activity of autophagy-associated genes was increased in the cumulus-oocyte complexes (COCs) following follicle-stimulating hormone (FSH) treatment, while the addition of luteinizing hormone (LH) reversed this effect. The expression of proteins associated with autophagy was the highest in FSH-treated COCs. On the other hand, caspase-3 protein level was maximum in COCs cultured with LH. The treatment with rapamycin resulted in the effect similar to that observed with FSH treatment and increased autophagy activity. Thus, hormonal stimulation of pig oocytes resulted in distinct patterns of maturation. The high-quality oocytes majorly relied on the type II pathway (autophagy), while the type I pathway (apoptosis) was more prominent among poor-quality oocytes. Further investigation of this distinction may allow the development of techniques to produce high-quality oocytes in porcine in vitro fertilization.